Chromatography-Independent Fractionation and Newly Identified Molecular Features of the Adzuki Bean (Vigna angularis Willd.) beta-vignin Protein - Philadelpho, Biane; Souza, Victoria; Souza, Fabiani; Santos, Johnnie; Batista, Fabiana; Silva, Mariana [UNESP]; Capraro, Jessica; De Benedetti, Stefano; Heinzl, Giuditta C.; Cilli, Eduardo [UNESP]; Scarafoni, Alessio; Magni, Chiara; et al. (Mdpi, 2021)
Adzuki seed beta-vignin, a vicilin-like globulin, has proven to exert various health-promoting biological activities, notably in cardiovascular health. A simple scalable enrichment procedure of this protein for further nutritional and functional studies is crucial. In this study, a simplified chromatography-independent protein fractionation procedure has been optimized and described. The electrophoretic analysis showed a high degree of homogeneity of beta-vignin isolate. Furthermore, the molecular features of the purified protein were investigated. The adzuki bean beta-vignin was found to have a native size of 146 kDa, and the molecular weight determined was consistent with a trimeric structure. These were identified in two main polypeptide chains (masses of 56-54 kDa) that are glycosylated polypeptides with metal binding capacity, and one minor polypeptide chain with a mass 37 kDa, wherein these features are absent. The in vitro analysis showed a high degree of digestibility of the protein (92%) and potential anti-inflammatory capacity. The results lay the basis not only for further investigation of the health-promoting properties of the adzuki bean beta-vignin protein, but also for a possible application as nutraceutical molecule.
Keywords: protein vicilin-type; protein fractionation; biological activities; in vitro digestibility; amino acid sequencing; glycosylated polypeptides; metal binding capacity